2019
DOI: 10.3847/1538-4357/ab50be
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the Interstellar Medium in Ultraluminous Infrared QSO Hosts with ALMA

Abstract: We present ALMA observations of the CO(1−0) line and 3-mm continuum emission in eight ultraluminous infrared (IR) quasi-stellar objects (QSOs) at z = 0.06−0.19. All eight IR QSO hosts are clearly resolved in their CO molecular gas emission with a median source size of 3.2 kpc, and seven out of eight sources are detected in 3-mm continuum, which is found to be more centrally concentrated with respect to molecular gas with sizes of 0.4−1.0 kpc. Our observations reveal a diversity of CO morphology and kinematics … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 134 publications
(184 reference statements)
6
19
0
Order By: Relevance
“…Its integrated flux density is 14.58 mJy, with the flux density of the tapered maps approximately similar. It exhibits starburst level star formation at a rate of 183 M yr −1 derived from the CO(1-0) luminosity (Tan et al 2019). This is evident also in our star formation diagnostics, as the W3-W4 colour is 2.88, q22 = 1.23, S W3 is 153.7 mJy higher than S 1.4GHz, JVLA (45.3 mJy).…”
Section: J0629-0545supporting
confidence: 76%
See 1 more Smart Citation
“…Its integrated flux density is 14.58 mJy, with the flux density of the tapered maps approximately similar. It exhibits starburst level star formation at a rate of 183 M yr −1 derived from the CO(1-0) luminosity (Tan et al 2019). This is evident also in our star formation diagnostics, as the W3-W4 colour is 2.88, q22 = 1.23, S W3 is 153.7 mJy higher than S 1.4GHz, JVLA (45.3 mJy).…”
Section: J0629-0545supporting
confidence: 76%
“…However, its radio luminosity, log νL ν,int = 40.43 erg s −1 , would be high even for a starburst galaxy, and thus it is plausible that radio emission is a combination of nuclear and star formation related processes. Tan et al (2019) in ALMA observations found a rotating gas disk with ordered velocity gradient, indicating that the host (Figs. B.2e and B.2f) is a disk galaxy which has not undergone any recent merger.…”
Section: J0629-0545mentioning
confidence: 93%
“…The jet-ISM collision interpretation is supported by the parameter η < 1 (Figure 6), which suggests that a dense environment hinders the expansion of the jet plasma 45 . Further support is provided by recent observations of I Zw 1 at other bands: the direction of the kilo-parsec-scale molecular gas disc was found 46,47 to be approximately along the parsec-scale jet direction here, and a radius of ∼7 mas (∼8 pc) torus is also proposed 48 .…”
supporting
confidence: 83%
“…Our observations reveal that the jet direction in I Zw 1 is along the kpc-scale molecular disk 46,47 , which is suggesting that the kpc-scale molecular disk (direction of the axis) is tilted with the inner accretion disk axis or BH spin. 51 , following the standard procedure.…”
mentioning
confidence: 66%
“…CO emission profiles have been used to estimate dynamical masses for individual objects since the early 2000s (Walter et al, 2003) even at fairly high redshift, and nowadays ALMA is rapidly adding to the available dynamical mass measurements for the host galaxy [e.g. (Tan et al, 2019;Molina et al, 2021)], considering that the velocity field of the molecular gas is often regular and consistent with rotation. State-of-the-art surface photometry of the AGN host galaxies in the NIR achieves decomposition in spheroid, disk, and bar component, as most of the host of nearby Seyfert galaxies are of morphological type Sa/SBa.…”
Section: The Virial Factor: Orientation and Radiation Effectsmentioning
confidence: 99%